Criminal Acts of Hate Speech Through Social Media During the Covid-19 Pandemic - Suhendar Suhendar; Nur Rohim Yunus; Annissa Rezki (SALAM: Jurnal Sosial dan Budaya Syar-i, 2023)
The rise of social media has facilitated communication between people, but it has also made it simpler to spread false information, which can lead to hate speech. At the height of the COVID-19 pandemic, all public gatherings were canceled, and people stayed home. Due to the ease with which information may be shared and disseminated and the difficulty in determining the authenticity of user claims, online hate speech is commonplace. The author incorporates legal research methods from qualitative and normative perspectives into this paper. As the results show, social media use has skyrocketed during the COVID-19 pandemic due to government restrictions on activities that can be carried out outside the home. Thus, many people like spending time on social media, and some even deliberately post remarks that amount to hate speech.Keywords: Crime; Hate Speech; Social media Abstrak Maraknya media sosial telah memfasilitasi komunikasi antar manusia, tetapi juga mempermudah penyebaran informasi palsu, yang dapat mengarah pada ujaran kebencian. Pada puncak pandemi COVID-19, semua pertemuan publik dibatalkan, dan orang-orang tetap tinggal di rumah. Karena mudahnya informasi dibagikan dan disebarluaskan serta sulitnya menentukan keaslian klaim yang dibuat oleh pengguna, ujaran kebencian online menjadi hal yang lumrah. Penulis memasukkan metode penelitian hukum baik dari perspektif kualitatif maupun normatif ke dalam makalah ini. Hasilnya, penggunaan media sosial meroket di masa pandemi COVID-19 sebagai akibat dari pembatasan pemerintah terhadap aktivitas yang boleh dilakukan di luar rumah. Sehingga, banyak orang yang suka menghabiskan waktu di media sosial, bahkan ada yang sengaja memposting ucapan yang berbau ujaran kebencian.Kata Kunci: Tindak Pidana; Ujaran Kebencian; Media Sosial